PERENCANAAN PERPIPAAN AIR BERSIH PADA BANGUNAN HOTEL DI KOTA PALU - Ibnu Fazhar (Universitas Kebangsaan, 2022)
The development of the city of Palu after the earthquake was increasingly rapid, this was due to the large number of revitalization of urban facilities and infrastructure buildings. Many people and workers need comfortable temporary housing. Hotel is a type of accommodation that is managed commercially by using part or all of the existing building to provide lodging, food and beverage service facilities. The construction of a hotel with the availability of clean water as a condition of comfort for its residents. For this reason, clean water facilities were built using a method that refers to SNI 03-7065-2005 (2005) concerning Procedures for Planning Plumbing Systems and SNI 8153-2015 for determining the dimensions of clean water pipes. The results of the calculation of the number of occupancy of visitors and hotel employees ranged from 134 people per day. Total clean water needs: 37.44 m3/day, Ground water tank capacity: 21.86 m3, roof tank capacity: 8.25 m3. Based on the design results of the 9.66 cm vertical pipe dimension, a centrifugal pump with a power of 2.76 kW is needed can be operated 15 minutes per hour.